GASTROPODS COMMUNITIES IN THE MANGROVE ECOSYSTEM WAISISIL BEACH SAPARUA DISTRICT MALUKU - Tetelepta, Lady (Universitas Pattimura, 2019)
The gastropods community in the mangrove ecosystem on the Waisisil beach, Saparua District, Maluku consists of 14 gastropod species, namely Clypeomorus batillariaeformis, Cypraea annulus, C. moneta, Hebra corticata, Littorina scabra, Morula margariticola, Nasarius olivaceus, Natica euzona, Nerita chamaeleon, N, signata, Otoplueura auriscati, Pyrene ocellata, Strombus labiatus, Terebralia sulcata. The species with the highest number of individuals was C. batillariaeformis and the species with the lowest number of individuals was C. annulus. The gastropod community in the mangrove ecosystem on the Waisisil beach has a species diversity index (H') = 1.8, evenness index (E) = 0.7, and dominance index (D) = 0.3.